(untitled) (Archives of Mechanics - Test, 2012)
The oscillatory flow of an incompressible couple stress fluid through an annulus with mild constriction at the outer wall is considered. The mean pressure drops and the mean wall shear stress are calculated across the constricted region. The steady streaming effect on the flow is presented. The variations in the mean pressure drop and wall shear stress with the size of the catheter, the velocity of the catheter and couple stress fluid parameter, are studied through graphs.